A content analysis of the promotional strategies employed by e-cigarette brands on Twitter. Issue 4 (2nd October 2019) - Alpert, Jordan M.; Jaisle, Alyssa; Chen, Huan
Abstract: Cigarette smoking in the U.S. is declining, but e-cigarette (e-cig) use is rapidly expanding. E-cig brands utilize social media for promotion and have the autonomy to disseminate messages that encourage the use of their products. The current study categorized the most frequent strategies among popular e-cig brands on Twitter. A content analysis of over 1800 tweets was performed based on Philip Morris brand personality characteristics. Most tweets emphasized e-cigs' economic value (24.2%) and normalized their use by portraying e-cigs as "cool" (23.1%). E-cig brands are employing similar strategies as tobacco companies and easily connecting to young adults through social media.